Towards a multidimensional model for assessing e-government service gaps - Mahlangu, Gilbert; Ruhode, Ephias (South African Journal of Information Management, 2020)
The term e-government is generally understood to mean the use of information technologies such as wide area networks, the Internet and mobile computing by government agencies to relate with citizens, businesses and other arms of government (Ngonzi & Sewchurran 2019). E-government is one of the foundations in the transformation drive of public service delivery. By implementing e-government, the majority of public services are expected to be provided electronically. The areas that have shown the most significant progress in the transformation drive of public service delivery include, but are not limited to, e-procurement; e-invoicing; e-payment; e-licensing; e-archiving; e-tendering; e-taxation; e-voting; e-democracy; e-submission; e-rental; e-compliance; e-assessment; e-participation; e-visa; e-health; e-learning; e-court; online passports, birth registration and permits applications; and online company registration (Baheer, Lamas & Samas 2020; Mukamurenzi, Grönlund & Islam 2019). Indeed, e-government is playing a critical role in transforming public services. Accordingly, the transformation drive in public service is facilitated by the following e-government delivery models: Government-to-Government (G2G); Government-to-Employees (G2E); Government-to-Business (G2B); and Government-to-Citizens (G2C) (Ahmad et al. 2019; Ramdan, Azizan & Saadan 2014; Voutinioti 2014). G2G represents the backbone platform for e-government adoption, implementation and utilisation in the entire country (Voutinioti 2014); G2E represents an internal relationship between the government and its employees (Ramdan et al. 2014);